Low-energy muon-transfer reaction from hydrogen isotopes to helium isotopes - Sultanov, R. A.; Adhikari, S. K. (Elsevier B.V., 2002)
Direct muon transfer in low-energy collisions of the muonic hydrogen H-mu and helium (He++) is considered in a three-body quantum-mechanical framework of coordinate-space integro-differential Faddeev-Hahn-type equations within two- and six-state close coupling approximations. The final-state Coulomb interaction is treated without any approximation employing appropriate Coulomb waves in the final state. This procedure of treating Coulomb interaction leads to much improved results for low-energy transfer rates. The present results agree reasonably well with previous semiclassical calculations. (C) 2002 Elsevier B.V. B.V. All rights reserved.